Corroborating the magnetic easy axis of epitaxial (100) α-iron and (0001) BaFe12O19 thin films by 57Fe Mössbauer spectroscopy - Y. E. Li; J. Shine; C. Guguschev; M. Brützam; D. G. Schlom; N. Ravi (AIP Advances)
60 and 120 nm thick epitaxial films of isotopically enriched bcc iron (α-57Fe) grown on (100) MgO substrates are studied using x-ray diffraction, reflection high-energy electron diffraction (RHEED), and conversion electron Mössbauer spectroscopy (CEMS). X-ray diffraction and RHEED data indicate that each film behaves as a single crystal material consistent with the relative intensity ratios of the spectral lines observed in the CEMS spectrum. Data further confirm that the easy axis of magnetization lies along the ⟨100⟩ family of directions of the cubic α-iron film. The relevant theory to understand the relative intensities in a magnetic Mössbauer spectrum is outlined and is applied to interpret the intensity ratio of the Mössbauer spectral lines of a more complex hexaferrite magnetic system, BaFe12O19, grown on a single crystal substrate of Sr1.03Ga10.81Mg0.58Zr0.58O19. The conclusion that the magnetic moment in (0001)-oriented epitaxial BaFe12O19 film lies perpendicular to the plane of the substrate is deduced from the absence of the second and fifth lines by comparing the CEMS spectrum of the epitaxial (0001) BaFe12O19 film with the spectrum of a polycrystalline BaFe12O19 powder. Our measurements using CEMS corroborate what is known about the direction of the magnetic easy axis in α-iron and BaFe12O19 and motivate the use of CEMS to probe more complex atomically engineered epitaxial heterostructures, including superlattices.